Can Social Media-Style Fanfiction Stories Enrich Students’ Narrative Writing Mastery? - Hadi, Muhamad Sofian; Karyadi, Aliya Nafisa (Journal of Languages and Language Teaching, 2023)
With the rise of pop culture, social media-style Fanfiction is a new style of fanfiction that are mostly read by students. However, students still find it hard to write narrative stories. This study is aimed at enhancing students’ narrative writing skills by employing social media-style Fanfiction stories as learning media. The design of the study is a pre-experimental design with one-group pre-test and post-test design. The samples of the study were 30 students from the eleventh grade of SMA Negeri 5 Depok. The data were collected using pre-test, treatment, and post-test and the data were calculated using a paired sample t-test to see the significant difference. Based on the data analysis, the findings showed that the students’ narrative writing skills were improved after using social media-style fanfiction as a learning media. In learning processes, students are involved in various writing activities such as practicing writing topic sentences, supporting sentences, and narrative features of narrative texts. It was proven with students’ writing achievement in the post-test. The score mean was increased from 66,58 to 81,04, and from the t-score it is -10,308 from t-table -2,045 which means that the hypothesis H1 is accepted. It can be concluded that the use of social media-style fanfiction story was able to enrich students’ narrative writing mastery at eleventh grade students.